Wojewódzkie mistrzostwa wsi ludowych zespołów sportowych. (Gdańsk : [s.n.], 1951)
Afisz inf. o zawodach 29.07.1951 r.
Keywords: Sport -- Polska -- 1945-1970 -- druki ulotne; Gdańskie, Województwo (Polska ; 1950-1974) -- druki ulotne